Managerial accounting - Braun, Karen Wilken; Tietz, Wendy M. (Always learning., 2018)
"Managerial Accounting helps readers see how managerial accounting concepts are used in business to make decisions. By presenting actual accounting decisions made in companies like Target and Macy's, the text's precise coverage of the core concepts better engages readers in the content. With new problems, cases, and applications in the 5th Edition, readers receive the most up-to-date information and practice opportunities to prepare them for their future careers in accounting"--Provided by Amazon.